Evaluation of cell viability of formulated fluconazole nanoemulgel by cytotoxicity analysis - RS, Narang; S, Srivastava; J, Ali; S, Baboota; B, Singh; SS, Kahlon; S, Dang; JK , Narang (International Journal of Psychosocial Rehabilitation, 2020)
Oral Candidiasis, also known as oral thrush among other names, is candidiasis that occurs in the oral cavity. Candida albicans is the most common species responsible for the disease. Fluconazole has a broad spectrum of activity and is currently the drug of choice for controlling oropharyngeal candidiasis, especially in patients suffering from AIDS. The aim of the present study was to evaluate the in vitro cytotoxicity and cell viability of fluconazole nanoemulgel formulated for the treatment of oral candidiasis. In vitro Vero cell line-based cytotoxicity analysis was performed using the MTT assay. It was observed that fluconazole-loaded nanoemulgel (FCZNE) showed dose-dependent cytotoxicity for the entire concentration range. Fluconazole-loaded nanoemulgel (FCZ-NE) exhibited cell viability of 100% to 76% for a concentration range of 2xCmax to 20xCmax, whereas fluconazole gel (FCZ) exhibited cell viability of 99% to 67% for the same concentration range. The results suggested that prepared fluconazole-loaded nanoemulgel (FCZ-NE) exhibited good cell viability in vitro, thus establishing its safety profile.